Variable-rate nitrogen application at the flag-leaf appearing stage is effective in increasing the grain protein content of the durum wheat - Keisuke Mizuta; Masanori Toyota; Masahiro Morokuma (Plant Production Science)
A high grain protein content (GPC) must be achieved in durum wheat cultivation. However, GPC is negatively correlated with the yield, making it difficult to control. In this study, we tested whether variable-rate nitrogen application at the flag-leaf appearing stage (GS37), where other operations are not overlapping in durum wheat cultivation, could effectively increase GPC. In addition, the possibility of using a growth diagnostic index calculated from canopy images as a guide to variable-rate nitrogen applications was tested. GPC was significantly increased by 0.8 to 2% for each 5 g m−2 increase in nitrogen application at GS37, which was due to an increase in aboveground nitrogen content of approximately 2 g m−2 for every 5 g m−2 increase in nitrogen. Although 44 growth diagnostic indices calculated from 2D images were tested, only the Hue 120–170° ratio showed a significant correlation with aboveground nitrogen content at GS37 over the three seasons, and no significant differences in intercept and slope were found over the three seasons. When the nitrogen content at GS37 was estimated using the Hue 120–170° ratio, and nitrogen was applied at GS37 to achieve 12 g m−2 aboveground nitrogen content at maturity, the nitrogen content in the validation plot at maturity was approximately 12 g m−2 irrespective of the sowing density. Therefore, variable-rate nitrogen application using 2D image diagnosis at GS37 would be an effective cultivation method to increase the GPC of durum wheat.